Blockchain-based dynamic energy management mode for distributed energy system with high penetration of renewable energy. (June 2023) - Wang, Longze; Jiang, Siyu; Shi, Yuyao; Du, Xinxin; Xiao, Yuxin; Ma, Yiyi; Yi, Xinxing; Zhang, Yan; Li, Meicheng
Highlights: A blockchain consensus mechanism is established by the proof of energy contribution. Energy contribution dynamically characterizes the data communication and energy interaction behavior of prosumers. Optimized blockchain encryption algorithm simplifies the model inversion process. Energy management mode reduces the network delay of distributed energy system. Abstract: The emerging blockchain technology is one of the most feasible solutions to decentralized and autonomous energy management in distributed energy systems (DESs). However, with the increase of renewable energy penetration in the DES, blockchain nodes will generate massive calculation tasks and cause high delay in energy trading. In this paper, we propose a dynamic energy management mode, which is tailored for the DES with high penetration of renewable energy. Firstly, a novel consensus mechanism is established by the proof of energy contribution. Particularly, the energy contribution value characterizes the credible transaction, emission reduction, demand response and system operation contribution of energy prosumers. Secondly, the model inversion process of blockchain SM2 encryption algorithm is simplified by using the verification data of nodes with high energy contribution, so as to improve the computation ability of the DES. Finally, an actual energy blockchain project with 300 renewable energy prosumers is analyzed as an example. The case study shows that this work can reduce the network delay to less than 2000 ms, which is more than double the operation efficiency of the energy trading in Ethereum. Moreover, by calculating the network delay under different conditions, it is concluded that the number of committee nodes has a greater impact on operational efficiency than the number of transactions in the new block and the total number of nodes.